An Investigation of Autonomous English Learners’ Personal Learning Environments - ปานกุล, กิติสุดา (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2020)
Learning autonomy is important for the learning process in the 21st century, not because of the exponential rate of technological advancement, but because it is about freedom of choice that is supportive to the learning process. This study focuses on learning autonomy in the sense of learners' ability to plan and control their own learning process. The process also includes the ability to re-plan and try again in case of failure. This helps shed some light on the fact that the learning process does not consist of a set of fixed steps, and that it is dynamic and adjustable because of uncertainty. The program, MacroSIM, was created in a virtual world as a language learning environment for an ESP course at tertiary level. Its design is underpinned by constructivist concepts and reduces irrelevant factors to the language learning. This article presents only qualitative findings which were analyzed from all participants’ diaries of the experimental group. The findings show that they could improve the structure of their learning process systematically after ten weeks of learning through the MacroSIM program. The investigation concludes with a model of self-driven language learning of 39 participants as language autonomous learners.